Stochasticity of two preys and one predator environmental framework utilizing Fourier tool - V.Madhusudanan; M.N.Srinivas (International Journal of Psychosocial Rehabilitation, 2020)
This article manages an investigation on numerical model of an ecological system with two prey, one predator and also within the sight of arbitrarily fluctuating main impetuses on the development of the species at time ’t’ of a customary eco framework. The model is depicted by a couple of non-direct differential conditions. Stochastic steadiness, as far as the fluctuations of the populaces of the given framework is inferred by using Fourier transform tool.